Knowledge, experiences, and practices of women affected by female genital schistosomiasis in rural Madagascar - Schuster, Angela; Rabozakandraina, Oliva Tiana Onintsoa; Randrianasolo, Bodo Sahondra; Ramarokoto, Charles Emile; Brønnum, Dorthe; Feldmeier, Hermann (Dryad, 2022)
Background: Female genital schistosomiasis (FGS) is a neglected
manifestation of urogenital schistosomiasis caused by S. haematobium. The
disease presents with symptoms such as pelvic pain, vaginal discharge and
bleeding and menstruation disorders, and might lead to infertility and
pregnancy complications.  The perspectives of women with FGS have
not been studied systematically. Methods: We performed a qualitative study
in the Ambanja district in Northwest Madagascar. FGS was diagnosed by
colposcopy. Seventy-six women with FGS participated either in a focus
group discussion (N=60) or in an individual semi-structured interview (N=
16). The data were analysed using Mayring´s qualitative content analysis.
The aim of the study was to understand knowledge, experiences, and
practices of women with FGS. Results: Knowledge on how the disease is
acquired varied and ideas on prevention remained vague. Patients suffered
from vaginal discharge and pelvic complaints. Some women expressed
unbearable pain during sexual intercourse and compared their pain to an
open wound being touched. FGS considerably impaired women´s daily
activities and their quality of life. Infertility led to resignation and
despair, conflicts with the partner and to social exclusion from the
community. Women fearing to sexually transmit FGS refrained from
partnership and sexual relations. Many women with FGS reported
stigmatisation. A coping strategy was to share strain with other women
having similar complaints. However, concealing FGS was a common behaviour
which led to social isolation and delayed health care seeking.
Conclusions: Our study underlines that FGS has an important impact on the
sexual health of women and on their social life in the community. Our
results highlight the importance of providing adequate health education
and structural interventions, such as the supply of water and the
provision of sanitation measures. Further, correct diagnosis and treatment
of FGS in adolescent girls and women should be available in all S.
haematobium-endemic areas.
The interviewers carried out semistructured interviews (SSI) and focus
groups discussions (FGD) in the villages Antsakoamanondro, Anjavimilay and
Ankazokony located in the Ambanja district. The interviews took place in a
room of the school or in a communal house in which privacy was guaranteed.
No other persons were allowed to attend the interview. Interviewers
captured non-verbal communication through written notes in a memo booklet.
SSI and FGD were audio recorded. We did not video record to avoid
intimidation. Sociodemographic information was retrieved from the
corresponding information from the RCT database. The authors revised the
interview guide based on the experiences with the first five SSI and the
first FGD. SSI and FGD were carried out between the 10th and the 17th of
April 2020 in a window of opportunity when COVID incidence in the region
was low. Due to time constraints in the context of COVID-19, we carried
out in depth data analysis only when all interviews where completed.
Therefore, saturation of the data could not be checked. We avoided
respondent validation (member checking) of the transcripts to prevent
social desirability bias. After transcription and translation, two authors
validated the translated transcripts by comparing them with the audio
recordings. Systematic differences between FGD and SSI where not noted,
thus both data sources were analysed jointly. Rules to define coding and
context units were developed based on the qualitative content analysis:
inductive categories were built thematically by paraphrasing and
generalising coding units, coding units were then attributed to the
deductive categories knowledge, attitudes and practice. Then the text
material was reduced in a two-step process into main and secondary
categories. The coding tree was built in an iterative manner through the
analysis of 20% of the material (3 SSI and 4 FGD). Intercoder differences
were brought together through discussions. The iterative adaptation of the
coding tree was finalised after the analysis of another 15% of the
material (2 SSI and 3 FGD, Figure 1). Two authors carried out
category-based analysis of the remaining interviews.
Qualitative data were analysed with Microsoft Excel (2010) using the
methodological approach in Figure 1. Methods and analysis were performed
based on the COREQ recommendations for standardised reporting of
qualitative research (39). Statistical analysis of the
sociodemographic data was performed using SPSS (Version 16.0; SPSS Inc,
Chicago, Illinois) since data did not follow normal distribution median
and range were calculated.
Keywords: Schistosomiasis; female genital schistosomiasis; Knowledge; attitudes; practices; KAP-Study; women; sexual and reproductive health; Stigma; social exclusion; Madagascar; FOS: Other medical sciences